Antenna-On-Chip Design, Challenges, and Opportunities. - Cheema, Hammad M. (Artech House, 2021)
Antennas are essential part of every wireless communication system. The increasing trend of applications in the radio frequency (RF) and millimeter wave frequency spectrum has reduced the antenna sizes to only a few millimeters, which makes it practical for on-chip implementations. Integrated Circuit (IC) designers who have traditionally remained isolated from antenna design now need to understand its design process and trade-offs. This comprehensive resource addresses the challenges, benefits and trade-offs of on-chip antenna implementation. It presents practical design and integration considerations of the IC and antenna combination and how both ends of the system can be utilized in a complimentary way. The book includes on-chip antenna layout considerations, layout for testability and various methods of their characterization. A look at the future trends and utilization of on-chip antennas for different applications concludes the book.